Photo‐Controlled Reversible Microtubule Assembly Mediated by Paclitaxel‐Modified Cyclodextrin. (21st June 2018) - Zhang, Ying‐Ming; Zhang, Ni‐Yuan; Xiao, Kui; Yu, Qilin; Liu, Yu
Abstract: The design and construction of multi‐stimuli‐responsive supramolecular nanoassemblies that can mimic and regulate the fundamental biological processes have become a focus of interest in supramolecular chemistry. In this work, a perfect combination has been achieved between naturally occurring microtubules and artificially macrocyclic receptors. The self‐assembling morphology of microtubules can be photo‐tuned by the host–guest interaction of paclitaxel‐modified β‐cyclodextrin (PTX‐CD) and photochromic arylazopyrazole (PTX‐AAP). Moreover, the supramolecularly aggregated microtubules in a cellular environment can induce a pronounced cell morphological change and cell death. This supramolecular approach based on the secondary PTX‐AAP⊂PTX‐CD complexation provides us a facile method to reversibly control the intertubular aggregation behaviors of microtubules, which may bring new perspectives in the treatment of diseases related to improper protein aggregation. Abstract : Eine Mikroröhren‐Anordnung lässt sich durch eine Wirt‐Gast‐Wechselwirkung von Paclitaxel‐modifiziertem Cyclodextrin und einem photochromen Arylazopyrazol mit Licht schalten und zeigt daher unterschiedliche Morphologien und Toxizitäten in Zellen.